The role of country tax environment on the relationship between financial derivatives and tax avoidance - Oktavia Oktavia; Sylvia Veronica Siregar; Ratna Wardhani; Ning Rahayu (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to examine the effect of financial derivatives usage and country’s tax environment characteristics on the relationship between financial derivatives and tax avoidance.This study uses a cross-country analysis with the scope of ASEAN (Association of Southeast Asian Nations) countries which consists of the Philippines, Indonesia, Malaysia, and Singapore.The level of financial derivatives usage positively affects the level of tax avoidance. This finding indicates that financial derivatives can be used as tax avoidance tool. Furthermore, the positive effect of the level of financial derivatives usage on the level of tax avoidance is lower in countries with a competitive tax environment than in countries with an uncompetitive tax environment. This finding indicates that in country with a competitive tax environment, the use of financial derivatives as a tax avoidance tool can be replaced by the tax facilities provided by that country.This study uses four countries in the Association of Southeast Asian Nations region and does not test the sample based on the financial derivative types.Tax authorities need to establish a clear tax regulation in regard to the tax treatment of financial derivatives transactions, e.g. define the definition of financial derivatives for hedging purposes and financial derivatives for speculative purposes; and define specific criteria to separate financial derivatives for hedging purposes from financial derivatives for speculative purposes. It is necessary to determine whether losses arising from derivative transactions are classified as deductible expenses or non-deductible expenses.To the best of the authors’ knowledge, this study is also the first that provide empirical evidence that the relationship between financial derivatives and tax avoidance activities depends on a country’s tax environment.